Review on Artificial Intelligence based Virtual Game Programs - Ranjan Das, Satya; Behera, Santosh (International Journal of Psychosocial Rehabilitation, 2025)
A significant percentage of individuals actively play computer games. In the amusement profession, gambling is growing faster every day. For fact, where there is human intelligence, both the customer and the living individual are concerned. Artificial intelligence is therefore extremely important if the game is more engrossing and customer-friendly. Because of the mobile phone boom, it can be observed that games are moving from boards to finger-held displays. In previous decades, great progress has been made in the field of Artificial Intelligence (AI). It is somewhat a flourishing area of work with a growing couple of crucial research areas as well as a reference implementation for a growing number of fields of implementation. In order to increase calculating strength due to hardware advances, AI frequently shows a rapid development, along with algorithmic innovations. AI has many practical uses in which the positive stories can be encountered in our everyday lives. Advances from AI have made it possible for users to learn pictures and expression, anger tracking, auto-driving cars, web page, AI-assisted creative design, multiplayer and several others